Enhancing Fatigue Life of Metal Parts Produced by High-Speed Laser Powder Bed Fusion Through In Situ Surface Quality Improvement - Daniel Ordnung; Mirko Sinico; Thibault Mertens; Han Haitjema; Brecht Van Hooreweder (Journal of Manufacturing and Materials Processing)
The poor surface quality of the metal parts produced by laser powder bed fusion limits their application in load-bearing components, as it promotes crack initiation under cyclic loadings. Consequently, improving part quality relies on time-consuming surface finishing. This work explores a dual-laser powder bed fusion strategy to simultaneously improve the productivity, surface quality, and fatigue life of parts with inclined up-facing surfaces made from a novel tool steel. This is achieved by combining building using a high layer thickness of 120 μm with in situ quality enhancement through powder removal and laser remelting. A bending fatigue campaign was conducted to assess the performance of such treated samples produced with different layer thicknesses (60 μm, hull-bulk 60/120 μm, 120 μm) compared to as-built and machined reference samples. Remelting consistently enhanced the fatigue life compared to the as-built reference samples by up to a factor of 36. The improvement was attributed to the reduced surface roughness, the reduced critical stress concentration factors, and the gradually changing surface features with increased lateral dimensions. This led to a beneficial load distribution and fewer potential crack initiation points. Finally, the remelting samples produced with a layer thickness of 120 μm enhanced the fatigue life by a factor of four and reduced the production time by 30% compared to the standard approach using a layer thickness of 60 μm.